Student attendace for final examination system - Mardiah, Johari (2015)
This project is developed by using the barcode scanner and student card to get the attendance of students during final exams at the end of each semester. Previously lecturers need to use paper to obtain the attendance of students. There are many problems when using paper as the paper include student attendance will be damaged and lost. This project can help lecturers to reduce such problems by designing automatically using barcode scanner attendance and student card. The system has been running with student card and get a code barcode scanner will detect the barcode number on the student card. Graphic User Interface (GUI) has been developed using Visual Basic 6.0 to create a database that is easier to access. In this system there is an admin who will control the overall in the system in which he will update all the data contained in this system. While users namely the invigilator only assigned to take student attendance and may view the data. Both actors in the system need to use the password and username that has been set by the admin. This shows the level of system security that cannot be accessed by others if they do not know the password and username. As an institution of higher education which is surrounded by various types of technology, they have moving together that does not seem far behind compared to other institutions in order to create a visionary state and quality from time to time.